False positive acetylcholine receptor antibodies in a case of unilateral chronic progressive external ophthalmoplegia: case report and review of literature. (3rd September 2018) - Rajput, Rehan; Sachdev, Amun; Din, Nizar; Damato, Erika Marie; Murray, Aidan
ABSTRACT: Methods: We present a rare case with atypical presenting features of unilateral CPEO with a false positive Acetylcholine Receptor Antibody (AchRA) test resulting in diagnostic delay. We illustrate the unilateral nature of this case and demonstrate the caveats of performing myogenic ptosis correction in such patients. We also discuss the differential diagnosis of false positive AchRA, a test commonly performed in the investigation of ptosis. Results: A 34-year old female presented with a more than 3-year history of slowly-progressive, unilateral, right-sided restriction in eye movements and ptosis. Clinical examination showed EOM were grossly restricted in the right eye with a ptosis and normal in the left eye. Serum AchRA was positive on serum enzyme-linked immunosorbent assay (ELISA) however, following two months of oral pyridostigmine therapy there were no signs of clinical improvement. The initial serum sample sent was retested for AchRA by radio-immunoassay (RIA) which came back negative. Subsequently a muscle biopsy was requested which showed the presence of ragged red fibres. Conclusion: Unilateral ptosis and ophthalmoplegia is an unusual presentation for CPEO which characteristically produces bilateral symmetrical motility defects. In addition to Myasthenia Gravis elevated AchRA levels have been reported in other autoimmune conditions such as Primary biliary cirrhosis, Eaton Lambert syndrome and Graves's ophthalmopathy. We also highlight the superiority of RIA versus ELISA in the detection of AchRA and illustrate the diagnostic challenge of investigating and managing myogenic ptosis in this complex cohort of patients.